The Effectiveness of Pojok Cerita (Po'rita) Counseling in Maintaining Mental Health of Adolescent - Widya Lita Fitrianur; Ervi Suminar; Wiwik Widiyawati; Putri Lidiah; Eka Febby Andrea (STIKes Patria Husada Blitar, 2024)
Adolescent mental health including anxiety, depression, bipolar disorder, and psychosis is a serious public health challenge because it can affect fundamental aspects of human life. One effort that can be made to maintain mental health is through Counseling as an intervention to solve mental problems. This research aimed to see the effectiveness of Counseling Pojok Cerita (Po'rita) in maintaining the mental health of teenagers. The research used a pre and post-test research design with a population of class X and XI students. Before the Counseling session, mental health screening was conducted using the Self-Reporting Questionnaire (SRQ). Out of 93 respondents, 43 students exhibited symptoms of mental health problems. The sampling technique employed was purposive sampling, targeting only students with identified mental health issues. The data were analyzed using the Paired T-test. Before the Counseling, all 43 students (100%) showed symptoms of neurosis (psychological issues), 37 (86%) exhibited psychotic symptoms, and all 43 students (100%) displayed symptoms of Post-Traumatic Stress Disorder (PTSD). After the Counseling, 19 (44%) still showed symptoms of neurosis, 17 (39%) exhibited psychotic symptoms, and 18 (42%) continued to display PTSD symptoms. There was a significant reduction in the number of students experiencing mental health problems post-counseling, with a p-value of 0.00<0.05. The Pojok Cerita (Po'rita) Counseling program is effective in maintaining the mental health of teenagers at SMA Negeri 1 Kebomas. It is recommended that the Po'rita Counseling program collaborate with school Counseling services to provide therapeutic interventions for adolescent mental health issues.